Damage mechanism of carbon-fiber-reinforced-plastic pipe based on reverse and forward curvature drilling. (15th July 2022) - Li, Shujian; Zou, Shi; Dai, Longyu; Zhou, Yongchao; Qiu, Xinyi; Li, Changping; Li, Pengnan; Jo Ko, Tae
Highlights: The one-time drilling method including reverse and forward curvature drilling is adopted for drilling small-diameter CFRP pipes. The damage behavior of drilling CFRP pipe is studied by the combination of theoretical analysis, finite element simulation, and experiment. The contact mode between the edge of drill bit and the arc surfaces of the upper and lower is different during CFRP pipe drilling. The machining quality of the CFRP pipe is better at low speed and low feed rate. Abstract: Metal-composite shaft parts composed of metal joints and composite pipes have attracted extensive attention in the fields of unmanned aerial vehicles (UAVs) and new energy vehicles because of their advantages of light weight, high strength, and stable axial load transmission. Hole making is a necessary process to ensure connections between a metal joint and composite pipe. For the drilling of small-diameter composite pipe, the one-time drilling method which including reverse and forward curvature drilling is usually used to ensure the stability of axial load transmission of the metal-composite shaft. An in-depth understanding of the damage mechanism of hole making in a composite pipe can help to guide hole making technology for composite pipes. In this study, the material damage mechanism of reverse and forward curvature drilling of carbon-fiber-reinforced-plastic (CFRP) pipe was analyzed by a theoretical analysis and finite element modeling and simulation. Verification experiments were designed to capture the cutting force and damage morphology of the entrance and exit. The effect of machining parameters on material damage is revealed, and reasonable suggestions are given for the selection of machining parameters in reverse and forward curvature drilling.